Silicon nitride substrate and method of producing the same
By manufacturing a silicon nitride substrate using silicon powder and optimizing the manufacturing process, the substrate achieves improved thermal conductivity and bending strength, overcoming the limitations of substrates made from silicon nitride powder.
Patent Information
- Application Number
- JP2023159066
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing silicon nitride substrates used in power modules face challenges in achieving high thermal conductivity and bending strength due to impurities and structural limitations, particularly when manufactured using silicon nitride powder.
A silicon nitride substrate is manufactured using silicon powder, which involves mixing a sintering aid with the silicon powder, forming a slurry, creating a sheet-like molded body, nitriding the silicon, and then densifying and sintering the substrate. This process aims to improve the microstructure and material properties of the substrate.
The resulting silicon nitride substrate exhibits enhanced thermal conductivity of 110 W/(m·K) or more and improved bending strength of 600 MPa or more, effectively addressing the limitations of substrates made from silicon nitride powder.
Smart Images

Figure 2025050340000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon nitride substrate and a manufacturing technique thereof, and more particularly to a silicon nitride substrate manufactured using silicon powder and a technique that is effectively applicable to the manufacturing technique thereof. [Background technology]
[0002] Japanese Patent Application Laid-Open No. 2018-184333 (Patent Document 1) describes a technology related to a silicon nitride substrate manufactured using silicon powder. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-184333 A Summary of the Invention [Problem to be solved by the invention]
[0004] For example, a power module is an electronic device that constitutes an inverter circuit that controls a motor installed in an electric vehicle, a hybrid electric vehicle, a railroad vehicle, or an industrial device. This power module includes a semiconductor device having a switching element used in the inverter circuit, and an insulating substrate (wiring substrate) mounted on this semiconductor device. Examples of the switching element include a power MOSFET and an IGBT (Insulated Gate Bipolar Transistor). When these switching elements are operated, heat is generated. That is, since heat is generated in the power module, it is necessary to prevent malfunctions and failures of the power module caused by heat.
[0005] Therefore, in order to efficiently dissipate the heat generated in the power module, the insulating substrate mounted on the semiconductor device is required to have high heat dissipation characteristics. In other words, the insulating substrate is required to have high thermal conductivity. In addition, the insulating substrate is also required to have improved bending strength. For this reason, there is a need for innovation to realize an insulating substrate having both high thermal conductivity and high bending strength. [Means for solving the problem]
[0006] The silicon nitride substrate in one embodiment includes a plurality of silicon nitride grains and a grain boundary phase existing between the plurality of silicon nitride grains. The density of the silicon nitride substrate is 3.15 g / cm 3 That's all.
[0007] Here, in the fracture surface generated by the bending strength test, a plurality of needle-like particles having a major axis diameter of 10 μm or more are present on the fracture surface.
[0008] In this case, the cumulative distribution of the major axis diameter of multiple acicular particles is L 50 is 33.0 μm or less, and the L of the cumulative distribution of the major axis diameter of multiple acicular particles is 90 is 72.0 μm or less, and the cumulative ratio of the major axis diameter of the plurality of acicular particles having a major axis diameter exceeding 100 μm is 3.5% or less.
[0009] The silicon nitride substrate in one embodiment includes a plurality of silicon nitride grains and a grain boundary phase existing between the plurality of silicon nitride grains. The density of the silicon nitride substrate is 3.15 g / cm 3 That's all.
[0010] Here, in the fracture surface generated by the bending strength test, a plurality of needle-like particles having a major axis diameter of 10 μm or more are present on the fracture surface.
[0011] In this case, the cumulative area distribution of multiple acicular particles is A 50 is 186μm 2 is the cumulative area distribution of multiple acicular particles, 90 is 560μm 2and the area is 800 μm 2 The cumulative area ratio of the plurality of acicular particles exceeding this range is 12.5% or less.
[0012] In one embodiment, a method for manufacturing a silicon nitride substrate includes the steps of: (a) mixing a sintering aid with silicon powder to prepare a mixed powder; (b) adding a dispersion medium to the mixed powder and pulverizing the mixture to prepare a slurry; (c) using the slurry to prepare a sheet-like molded body; (d) nitriding the silicon contained in the molded body; and (e) after step (d), sintering the molded body to densify it.
[0013] Here, in silicon powder, the cumulative volume distribution d 10 is 1.0 μm or more and 2.5 μm or less, and the cumulative volume distribution d 50 is 6.0 μm or more and 10.0 μm or less, and the cumulative volume distribution d 90 is 12.0μm or more and 20.0μm or less, and the specific surface area is 1.5m 2 / g or more 3.0m 2 / g or less. In addition, in the mixed powder, the cumulative volume distribution d 50 is 2.0 μm or more and 6.4 μm or less, and the cumulative volume distribution d 90 is 4.0μm or more and 11.0μm or less, and the specific surface area is 4.5m 2 / g or more 13.0m 2 The heating temperature in the step (d) is 1340° C. or more and 1450° C. or less, and the heating temperature in the step (e) is 1850° C. or more and 1950° C. or less. Effect of the Invention
[0014] According to the insulating substrate of the embodiment, it is possible to realize both an improvement in bending strength and an improvement in thermal conductivity. [Brief description of the drawings]
[0015] [Figure 1] 1 is a flowchart showing a manufacturing process of a silicon nitride substrate. [Diagram 2]1 is a graph illustrating d10, d50 and d90 in cumulative volume distribution. [Diagram 3] FIG. 1 is a diagram showing an image of a bending strength test. [Figure 4] 1 is a flowchart showing a procedure for quantifying a "microstructure." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In all the drawings for explaining the embodiments, the same members are generally designated by the same reference numerals, and the repeated explanations thereof will be omitted. In addition, hatching may be applied even to plan views in order to make the drawings easier to understand.
[0017] <Background to the review> In this embodiment, a silicon nitride substrate will be taken as an insulating substrate for explanation.
[0018] For example, there is a technology for manufacturing a silicon nitride substrate using silicon nitride powder. The thermal conductivity of the silicon nitride substrate manufactured by this technology is about 90 W / (m·K). In this regard, the present inventor has studied how to improve the thermal conductivity of the silicon nitride substrate, and has found that it is difficult to further improve the thermal conductivity with this technology due to the use of silicon nitride powder. That is, the present inventor has found that it is difficult to further improve the thermal conductivity because silicon nitride powder contains a lot of impurities and it is difficult to obtain high-purity silicon nitride powder. Specifically, it has been found that the silicon nitride substrate manufactured using silicon nitride powder has a high oxygen content, and it is difficult to improve the thermal conductivity of the silicon nitride substrate due to the high oxygen content.
[0019] Therefore, the use of silicon powder instead of silicon nitride powder is being considered. This is because silicon powder contains fewer impurities than silicon nitride powder, and it is easy to obtain high-purity silicon powder. In other words, since silicon powder has a higher purity than silicon nitride powder, it is thought that the decrease in thermal conductivity caused by impurities can be suppressed. Specifically, in a silicon nitride substrate manufactured using silicon powder, the oxygen content can be reduced, and as a result, the thermal conductivity of the silicon nitride substrate can be improved. For this reason, in this embodiment, a method for manufacturing a silicon nitride substrate using silicon powder instead of silicon nitride powder is adopted.
[0020] <Findings that the present inventors have focused on> When a silicon nitride substrate is observed under magnification, it is seen that the silicon nitride substrate has a structure (hereinafter referred to as "microstructure") that is composed of a plurality of silicon nitride grains that constitute the main phase, and a grain boundary phase (glass phase) that exists between the plurality of silicon nitride grains. For example, the grain boundary phase contains a sintering aid. This "microstructure" and the material properties of the silicon nitride substrate are closely related. In particular, the "microstructure" of a silicon nitride substrate manufactured using silicon powder contains acicular particles made of silicon nitride grains. The presence of these acicular particles may affect the material properties of the silicon nitride substrate.
[0021] For example, in the "microstructure" of a silicon nitride substrate manufactured using silicon nitride powder, there are almost no acicular particles composed of silicon nitride particles. In contrast, in the "microstructure" of a silicon nitride substrate manufactured using silicon powder, acicular particles are present. For this reason, the inventors have newly discovered that the structure in which acicular particles exist in the "microstructure" is unique to silicon nitride substrates manufactured using silicon powder, and that the material properties of silicon nitride substrates manufactured using silicon powder are determined by the presence of acicular particles in the "microstructure." In this specification, acicular particles with a major axis diameter of 10 μm or more are defined as "coarse acicular particles."
[0022] Specifically, when focusing on silicon nitride substrates manufactured using silicon powder, it is known that there is a relationship between the acicular particles (silicon nitride particles) of the main phase that constitutes the "microstructure" and bending strength, and that bending strength decreases due to an increase in the size of the acicular particles or the presence of abnormally grown particles. As for thermal conductivity, as the size of the acicular particles increases, the proportion of silicon nitride particles with high thermal conductivity increases, and the thermal conductivity of the silicon nitride substrate improves.
[0023] Therefore, it can be seen that there is a trade-off between the improvement of bending strength and the improvement of thermal conductivity with respect to the size of the acicular particles. Therefore, in order to realize both the improvement of bending strength and the improvement of thermal conductivity, it is important to find a "microstructure" that can realize both the improvement of bending strength and the improvement of thermal conductivity by focusing on the acicular particles of the "microstructure" that is closely related to the material properties. This will be explained in more detail below.
[0024] In the method of manufacturing a silicon nitride substrate using silicon powder, a nitriding step is required to change silicon particles into silicon nitride particles. In this nitriding step, after the phase change from silicon particles to silicon nitride particles occurs, a phase transition from α-type silicon nitride particles to β-type silicon nitride particles occurs. Here, it is difficult to control the abundance ratio and particle size distribution of α-type silicon nitride particles and β-type silicon nitride particles, which results in the scattering of β-type silicon nitride particles whose particle size is difficult to control. Then, after the nitriding step, a densification sintering step is carried out to achieve densification. At this time, coarse acicular particles grow in the "microstructure" with the above-mentioned β-type silicon nitride particles as nuclei. The growth of the coarse acicular particles causes a problem that the thermal conductivity of the silicon nitride substrate is improved, while the bending strength is reduced. Therefore, in the current situation, it is difficult to manufacture a silicon nitride substrate that can realize both improved bending strength and improved thermal conductivity using a method of manufacturing a silicon nitride substrate using silicon powder.
[0025] Therefore, in this embodiment, in a method for manufacturing a silicon nitride substrate using silicon powder, the manufacturing conditions are devised to improve the performance of the silicon nitride substrate. In this embodiment, the "microstructure" of the silicon nitride substrate obtained by devising the manufacturing conditions is analyzed to identify a "microstructure" structure that can achieve both improved bending strength and improved thermal conductivity. The technical concept of this embodiment is described below.
[0026] <Basic Concept of the Embodiment> The method for producing a silicon nitride substrate using silicon powder includes the following steps. (a) mixing a sintering aid with a silicon powder to prepare a mixed powder; (b) adding a dispersion medium to the mixed powder and grinding the mixture to prepare a slurry; (c) preparing a sheet-like compact using the slurry; (d) nitriding the silicon contained in the molded body; (e) A step of densifying and sintering the green body after the step (d).
[0027] In the method for producing a silicon nitride substrate using such silicon powder, the basic idea of the present embodiment prescribes the production conditions shown below. 1. Cumulative volume distribution and specific surface area of silicon powder 2.Specifying the cumulative volume distribution and specific surface area of the mixed powder after grinding 3. Heating temperature range in the nitriding process 4. Heating temperature range in the sintering process This basic concept makes it possible to improve the performance of the silicon nitride substrate. Hereinafter, an embodiment that embodies this basic concept will be described.
[0028] <Embodiment> <<Method of manufacturing silicon nitride substrate>> A method for manufacturing a silicon nitride substrate employed in the embodiment will be described below.
[0029] FIG. 1 is a flow chart showing the steps of manufacturing a silicon nitride substrate according to an embodiment.
[0030] 1. Slurry preparation process In the embodiment, a sintering aid is mixed with silicon powder to prepare a mixed powder (S101). Then, for example, a rare earth element oxide and a magnesium compound are added as sintering aids to the silicon powder to prepare a mixed powder, and a slurry is prepared using the mixed powder (S102).
[0031] <<<Silicon>>> In the embodiment, silicon powder of industrially available grade can be used. The silicon before pulverization is preferably a powder having an oxygen content of 1.0 mass% or less and an impurity carbon content of 0.15 mass% or less. More preferably, the powder has an oxygen content of 0.5 mass% or less and an impurity carbon content of 0.10 mass% or less.
[0032] In particular, the purity of the silicon powder is preferably 99% or more, and more preferably 99.5% or more, because the impurity oxygen contained in silicon is one of the factors that inhibit the thermal conduction of the silicon nitride substrate obtained by reactive sintering, and therefore, from the viewpoint of improving the thermal conductivity of the silicon nitride substrate, it is preferable that the impurity oxygen is as small as possible.
[0033] Furthermore, it is desirable to adjust the mixed powder so that the total amount of impurity oxygen contained in the silicon powder and oxygen from the magnesium compound is in the range of 0.1% by mass to 1.1% by mass based on silicon converted to silicon nitride by limiting the amount of oxygen from the magnesium compound. Also, the impurity carbon contained in silicon inhibits the growth of silicon nitride particles in the silicon nitride substrate obtained by reaction sintering, which tends to result in insufficient densification, and this is one of the factors that lead to a decrease in the thermal conductivity and insulation properties of the silicon nitride substrate, so it is desirable to have as little impurity carbon as possible.
[0034] Here, the silicon powder used in the embodiment has the following characteristics: (1) Cumulative volume distribution d 10 is 1.0 μm or more and 2.5 μm or less. (2) Cumulative volume distribution d 50 is 6.0 μm or more and 10.0 μm or less. (3) Cumulative volume distribution d 90 is 12.0 μm or more and 20.0 μm or less. (4) The BET specific surface area is 1.5 m 2 / g or more 3.0m 2 / g or less.
[0035] In this specification, the BET specific surface area (m 2 / g) is a value obtained by a BET specific surface area meter using the BET single point method (JIS R 1626:1996 "Method of measuring the specific surface area of fine ceramic powders by the gas adsorption BET method"). 10 (μm) is the particle size at which the cumulative frequency is 10% in the cumulative volume distribution obtained by the laser diffraction / scattering method. Similarly, d 50 (μm) is the particle size (median diameter) when the cumulative frequency is 50% in the cumulative volume distribution, and d 90 (μm) is the particle size at which the cumulative frequency is 90% in the cumulative volume distribution.
[0036] <<<Rare earth element oxides>>> In an embodiment, the rare earth element oxide used is an oxide of yttrium (Y), ytterbium (Yb), gadolinium (Gd), erbium (Er), lutetium (Lu), or the like, which is easy to obtain and stable as an oxide.
[0037] Specifically, the rare earth element oxide is yttrium oxide (Y 2 O 3 ), Ytterbium oxide (Yb 2 O 3 ), gadolinium oxide (Gd 2 O 3 ), erbium oxide (Er 2 O 3 ), lutetium oxide (Lu 2 O3 ) etc.
[0038] The content of rare earth element oxide is, for example, 0.5 mol% or more and less than 2 mol% based on the total of silicon (converted to silicon nitride), rare earth element oxide (converted to trivalent oxide), and magnesium compound (converted to MgO). If the content of rare earth element oxide is less than 0.5 mol%, the effect as a sintering aid is insufficient, and the density is not sufficiently high. On the other hand, if the content of rare earth element oxide is 2.0 mol% or more, the grain boundary phase with low thermal conductivity increases, so that the thermal conductivity of the sintered body decreases and the amount of expensive rare earth element oxide used increases. In particular, the content of rare earth element oxide is preferably 0.6 mol% or more and less than 2 mol%, and more preferably 1 mol% or more and 1.8 mol% or less.
[0039] In this specification, silicon nitride (Si) is obtained when all silicon is nitrided. 3 N 4 ) and the number of moles of rare earth oxides divided into trivalent oxides (RE 2 O 3 The sum of the number of moles of silicon (converted to silicon nitride), rare earth element oxides (converted to trivalent oxides), and magnesium compounds (converted to MgO) is sometimes simply referred to as the "sum of silicon (converted to silicon nitride), rare earth element oxides (converted to trivalent oxides), and magnesium compounds (converted to MgO)."
[0040] <<<Magnesium compounds>>> As the magnesium compound, one or more magnesium compounds containing "Si", "N" or "O" can be used. In particular, magnesium oxide (MgO), magnesium silicon nitride (MgSiN 2 ), magnesium silicide (Mg 2 Si), magnesium nitride (Mg 3 N 2 ) is preferable.
[0041] Here, the magnesium silicon nitride is selected so that 87% by mass or more of the total amount of magnesium compounds is magnesium silicon nitride. By using 87% by mass or more of magnesium silicon nitride, the oxygen concentration in the obtained silicon nitride substrate can be reduced. If the magnesium silicon nitride content in the magnesium compound is less than 87% by mass, the amount of oxygen in the silicon nitride particles after sintering increases, resulting in a decrease in the thermal conductivity of the sintered body (silicon nitride substrate). Therefore, from the viewpoint of improving the thermal conductivity of the silicon nitride substrate, it is desirable for the magnesium silicon nitride content in the magnesium compound to be as high as possible, for example, 90% by mass or more.
[0042] The content of magnesium compound in the silicon nitride substrate (in terms of MgO) is, for example, 8 mol% or more and less than 15 mol% based on the total of silicon (in terms of silicon nitride), rare earth element oxide (in terms of trivalent oxide), and magnesium compound (in terms of MgO). If the content of magnesium compound is less than 8 mol%, the effect as a sintering aid is insufficient, and the density is not sufficiently high. On the other hand, if the content of magnesium compound is 15 mol% or more, the thermal conductivity of the sintered body decreases due to an increase in the grain boundary phase with low thermal conductivity. In particular, the content of magnesium compound is preferably 8 mol% or more and less than 14 mol%, and more preferably 9 mol% or more and 11 mol% or less.
[0043] A slurry is prepared using the silicon, rare earth element oxide, and magnesium compound described above (S102). Specifically, a mixed powder is prepared by adding a rare earth element oxide and a magnesium compound as a sintering aid to silicon powder in a predetermined ratio, and then a dispersion medium (organic solvent) and, if necessary, a dispersant are added, and the mixture is pulverized in a ball mill to prepare a slurry, which is a dispersion of the mixed powder. As the dispersion medium, ethanol, n-butanol, toluene, etc. can be used. As the dispersant, for example, a sorbitan ester type dispersant, a polyoxyalkylene type dispersant, etc. can be used.
[0044] The amount of the dispersion medium used is preferably, for example, 40% by mass or more and 70% by mass or less with respect to the total amount of the mixed powder, and the amount of the dispersant used is preferably, for example, 0.3% by mass or more and 2% by mass or less with respect to the total amount of the mixed powder. After dispersion, the dispersion medium may be removed or replaced with another dispersion medium as necessary.
[0045] Here, the mixed powder after pulverization contained in the slurry has the following characteristics. (5) Cumulative volume distribution d 50 is not less than 2.0 μm and not more than 6.4 μm. (6) Cumulative volume distribution d 90 is 4.0 μm or more and 11.0 μm or less. (7) The BET specific surface area is 4.5m 2 / g or more 13.0m 2 / g or less.
[0046] 2. Compaction manufacturing process To the slurry obtained as described above, for example, a dispersion medium, an organic binder, a dispersant, etc. are added, and vacuum degassing is performed as necessary, and then the viscosity is adjusted to a predetermined range to prepare a coating slurry.
[0047] Next, the prepared coating slurry is formed into a sheet using a sheet forming machine, cut into a predetermined size, and then dried to prepare a sheet-like molded product (S103).
[0048] The organic binder used to prepare the coating slurry is not particularly limited, but examples thereof include PVB resin (polyvinyl butyral resin), ethyl cellulose resin, acrylic resin, etc. The amounts of the dispersion medium, organic binder, dispersant, etc. added are desirably adjusted appropriately according to the coating conditions.
[0049] The method for forming the coating slurry into a sheet is not particularly limited, but sheet forming methods such as a doctor blade method and an extrusion molding method can be used.
[0050] The thickness of the sheet-like molded body formed in the molded body preparation step is, for example, 0.15 mm to 0.8 mm. The prepared sheet-like molded body is cut to a predetermined size using, for example, a punching machine, as necessary.
[0051] 3. Sintering process The sheet-like molded body thus produced is heated to nitride the silicon contained in the molded body, and then a sintering step is carried out to densify the molded body (S104). This sintering step includes a degreasing step (S104A) for removing the organic binder contained in the molded body, a nitriding step (S104B) for reacting the silicon contained in the molded body with nitrogen to form silicon nitride, and a densification sintering step (S104C) carried out after the nitriding step. These steps may be carried out sequentially in separate furnaces, or may be carried out continuously in the same furnace.
[0052] In the sintering process, for example, the prepared sheet-like compacts are stacked on a setter made of boron nitride (BN) with a separator sandwiched therebetween, and a weight is placed on the top layer of the stacked compacts, which are then placed in an electric furnace. In this state, an organic binder removal process (degreasing process) is performed, and then a decarbonization process is performed in a nitriding device at a temperature of 900°C to 1300°C, and the temperature is raised to a temperature of 1340°C to 1450°C in a nitrogen atmosphere to perform a nitriding process. Thereafter, a densification sintering process is performed in a sintering device at a temperature of 1850°C to 1950°C. Such a sintering process is performed while applying a load of 10 Pa to 1000 Pa to the compact, for example, by a weight.
[0053] Here, the heating conditions in the embodied embodiment are as follows. (8) The heating temperature in the nitriding step is 1340°C or higher and 1450°C or lower. (9) The heating temperature in the densification sintering step is 1850°C or higher and 1950°C or lower.
[0054] In this manner, a silicon nitride substrate can be manufactured.
[0055] The silicon nitride substrate thus manufactured has the following characteristics: (A1) Density: 3.15g / cm 3 That's all. (B1) Thermal conductivity is 110 W / (m K) or more. (C1) The bending strength is 600 MPa or more. (D1) Fracture toughness is 6 MPa m 0.5 That's all.
[0056] Therefore, according to the embodiment, the performance of the silicon nitride substrate can be improved. That is, according to the embodiment, in the method for producing a silicon nitride substrate using silicon powder, by adopting the above-mentioned production conditions, both improved bending strength and improved thermal conductivity can be realized. For example, according to the embodiment, it is possible to produce a silicon nitride substrate having a bending strength of 600 MPa or more while having a thermal conductivity of 110 W / (m K) or more.
[0057] <<Structure of silicon nitride substrate>> The silicon nitride substrate manufactured under the above-mentioned manufacturing conditions has both high thermal conductivity and high bending strength. Here, the properties of the silicon nitride substrate, such as thermal conductivity and bending strength, are closely related to the "microstructure" constituting the silicon nitride substrate. For this reason, the "microstructure" of the silicon nitride substrate manufactured under the above-mentioned manufacturing conditions has a composition that realizes high thermal conductivity and high bending strength. Therefore, if the "microstructure" of the silicon nitride substrate manufactured under the above-mentioned manufacturing conditions can be analyzed by some means, the "microstructure" that realizes high thermal conductivity and high bending strength can be quantitatively identified.
[0058] Therefore, in the embodiment, the "microstructure" is analyzed using image analysis techniques.
[0059] 1. Application of image analysis technology (first characteristic in the embodiment mode) To analyze the "microstructure," an image of the "microstructure" is used. Specifically, in the embodiment, an SEM image of a fracture surface generated by a bending strength test is used.
[0060] FIG. 3 is a diagram showing an image of a bending strength test.
[0061] As shown in Fig. 3, a load is applied to the silicon nitride substrate 10. As the load applied to the silicon nitride substrate 10 is increased, the silicon nitride substrate 10 breaks. The bending strength of the silicon nitride substrate 10 is measured based on the load at this time. An SEM image of the fracture surface of the fractured silicon nitride substrate 10A or silicon nitride substrate 10B is then obtained. In this embodiment, an SEM image of the fracture surface can be obtained as an image of the "microstructure".
[0062] The properties of silicon nitride substrates are closely related to their "microstructures." In particular, silicon nitride substrates manufactured using silicon powder have acicular particles in their "microstructures." The coarse acicular particles have a significant effect on the properties of silicon nitride substrates. Therefore, in the embodiment, image analysis technology is used to extract the coarse acicular particles contained in the SEM images of the fracture surface. For this reason, in the embodiment, the major axis diameter or area of the acicular particles is used as a parameter for extracting the coarse acicular particles from the SEM images of the fracture surface.
[0063] 2. Use of statistical processing (second feature of the embodiment) For example, there are studies that evaluate the relationship between the quantification of "microstructure" by image analysis and the properties of silicon nitride substrates. However, in these studies, the number of observation images that are the subject of image analysis is small, at only a few, and therefore the analysis results may be significantly affected by the observation images selected. In other words, the results of these studies may not be fully objective analysis results.
[0064] In this regard, in the embodiment, when quantifying based on the coarse acicular particles contained in the "microstructure", statistical processing is performed using many observation images. As a result, according to the embodiment, it is possible to obtain an analysis result with more objective reliability. In other words, by using statistical processing based on many observation images, it is possible to realize quantification of the "microstructure" that has a precise correlation with the characteristics. For example, in the embodiment, by using the major axis diameter or the area of the acicular particles as a parameter, the coarse acicular particles are extracted from multiple SEM images of the fracture surface, and then the major axis diameter cumulative distribution or area cumulative distribution is calculated from the extracted coarse acicular particles by statistical processing. As a result, according to the embodiment, it is possible to realize quantification of the "microstructure" based on the calculated major axis diameter cumulative distribution or area cumulative distribution.
[0065] For example, if the major axis diameter cumulative distribution or the area cumulative distribution can be obtained, the "microstructure" can be quantitatively specified by defining the characteristics of the major axis diameter cumulative distribution or the characteristics of the area cumulative distribution.
[0066] Specifically, the cumulative distribution of the long axis diameter is characterized by L 50 , L 90 and the cumulative ratio of major axis diameters having a major axis diameter equal to or greater than a predetermined value. Here, L 50 (μm) is the major axis diameter when the cumulative frequency is 50% in the cumulative distribution of major axis diameters. 90 (μm) is the major axis diameter when the cumulative frequency is 90% in the major axis diameter cumulative distribution.
[0067] Similarly, the area cumulative distribution is characterized by A 50 , A 90 and the cumulative ratio of areas having an area equal to or greater than a predetermined value. 50 (μm 2 ) is the area when the cumulative frequency is 50% in the area cumulative distribution. Also, A 90 (μm 2 ) is the area when the cumulative frequency is 90% in the area cumulative distribution.
[0068] To summarize the above, quantification of the "microstructure" is carried out in the following steps.
[0069] FIG. 4 is a flow chart showing the procedure for quantifying the "microstructure."
[0070] In FIG. 4, first, SEM images (200x) of fracture surfaces generated by bending strength tests are obtained, 40 to 50 per fracture surface (S201). Next, from each of the obtained SEM images, coarse acicular particles with a major axis diameter of 10 μm or more are extracted (S202), for example, by an automatic recognition technique using machine learning. After that, the major axis diameter or area of each of the extracted coarse acicular particles is calculated by data analysis (S203). Next, a major axis diameter cumulative distribution or area cumulative distribution is obtained based on the calculated major axis diameter or area (S204). Then, the "microstructure" is quantified based on the major axis diameter cumulative distribution or area cumulative distribution (S205). For example, L 50 , L 90 By specifying the cumulative ratio of the major axis diameter having a major axis diameter of a predetermined value or more, it is possible to quantitatively specify the structure of the "microstructure" that can realize both improvement in bending strength and improvement in thermal conductivity. In addition, as another method for quantitatively specifying the structure of the "microstructure", A is determined based on the cumulative distribution of area. 50 , A 90 A technique for identifying the cumulative area ratio having an area equal to or greater than a predetermined value can also be used. In this manner, the structure of the "microstructure" can be quantitatively defined from the SEM image of the fracture surface generated by the bending strength test.
[0071] 3. Quantitative results of "microstructure" (third characteristic of the embodiment) <<<Quantification of "microstructure" based on cumulative distribution of major axis diameter>>> In a silicon nitride substrate manufactured under the manufacturing conditions in the embodied embodiment, based on the cumulative distribution of major axis diameter, the "microstructure" constituting the silicon nitride substrate can be quantitatively defined as shown below, assuming that a plurality of acicular particles having a major axis diameter of 10 μm or more are present on the fracture surface generated by a bending strength test. (1) L of the cumulative distribution of the major axis diameter of multiple acicular particles 50 is less than 33.0 μm. (2) L of the cumulative distribution of the major axis diameter of multiple acicular particles 90 is less than 72.0 μm. (3) The cumulative ratio of the major axis diameter of a plurality of acicular particles having a major axis diameter exceeding 100 μm is 3.5% or less. A silicon nitride substrate including a "microstructure" quantitatively defined as above has the following characteristics. This is because a silicon nitride substrate having a "microstructure" having the above-mentioned characteristics is a silicon nitride substrate manufactured under the manufacturing conditions in the embodied embodiment, and a silicon nitride substrate manufactured under the manufacturing conditions in the embodied embodiment has the following characteristics. (A1) Density: 3.15g / cm 3 That's all. (B1) Thermal conductivity is 110 W / (m K) or more. (C1) The bending strength is 600 MPa or more. (D1) Fracture toughness is 6 MPa m 0.5 That's all.
[0072] Here, the quantification of the "microstructure" can be performed not only based on the cumulative distribution of major axis diameter, but also based on the cumulative distribution of area. The quantification of the "microstructure" based on the cumulative distribution of area will be described below.
[0073] <<<Quantification of "microstructure" based on cumulative area distribution>>> In a silicon nitride substrate manufactured under the manufacturing conditions in the embodied embodiment, based on the area cumulative distribution, the "microstructure" constituting the silicon nitride substrate can be quantitatively defined as shown below, assuming that a plurality of acicular particles having a major axis diameter of 10 μm or more are present on the fracture surface generated by a bending strength test. (1) A of the cumulative area distribution of multiple acicular particles 50 is 186μm 2 The following is the result. (2) A of the cumulative area distribution of multiple acicular particles 90 is 560μm 2The following is the result. (3) Area is 800 μm 2 The cumulative area ratio of the plurality of acicular particles exceeding A is 12.5% or less. 50 (μm 2 ) is the area when the cumulative frequency is 50% in the area cumulative distribution. Also, A 90 (μm 2 ) is the area when the cumulative frequency in the cumulative area distribution is 90%. The silicon nitride substrate in this case also has the above-mentioned characteristics. This is because the silicon nitride substrate having a "microstructure" quantitatively defined based on the cumulative area distribution is a silicon nitride substrate manufactured under the manufacturing conditions in the embodied aspect, and the silicon nitride substrate manufactured under the manufacturing conditions in the embodied aspect has the above-mentioned characteristics.
[0074] <<Effects in the realization mode>> According to the embodiment, the performance of the silicon nitride substrate can be improved, thereby expanding the range of options for the thickness of the copper wiring formed on the upper surface of the silicon nitride substrate, for example.
[0075] Specifically, by improving the thermal conductivity, the thickness of the copper wiring required to obtain a predetermined thermal resistance value can be reduced in a wiring board (a board including a silicon nitride board and copper wiring formed on the upper surface of the board). As a result, according to the embodiment, it is possible to reduce the amount of copper material, reduce manufacturing costs by speeding up the etching process, and realize high-density packaging by miniaturizing the copper wiring.
[0076] In addition, since the bonding strength between the silicon nitride substrate and the copper wiring is improved due to the improved bending strength, the thickness of the copper wiring can be increased to improve the heat dissipation characteristics. As a result, according to the embodiment, the cooling system of the power module including the wiring substrate can be simplified and the power module can be made smaller.
[0077] <Modification> Below, a modified example in which the manufacturing conditions are changed will be described.
[0078] The manufacturing conditions used in this modification are as follows:
[0079] The silicon powder used in this variant has the following characteristics: (1) Cumulative volume distribution d 10 is 1.0 μm or more and 2.5 μm or less. (2) Cumulative volume distribution d 50 is not less than 6.0 μm and not more than 9.5 μm. (3) Cumulative volume distribution d 90 is 12.0 μm or more and 20.0 μm or less. (4) The BET specific surface area is 1.5 m 2 / g or more 3.0m 2 / g or less.
[0080] In this modification, the mixed powder after pulverization contained in the slurry has the following characteristics. (5) Cumulative volume distribution d 50 is 2.0 μm or more and 6.0 μm or less. (6) Cumulative volume distribution d 90 is 4.0 μm or more and 9.2 μm or less. (7) The BET specific surface area is 4.5m 2 / g or more 13.0m 2 / g or less.
[0081] In this modified example, the heating conditions are as follows. (8) The heating temperature in the nitriding step is 1350°C or higher and 1450°C or lower. (9) The heating temperature in the densification sintering step is 1850°C or higher and 1950°C or lower.
[0082] The silicon nitride substrate manufactured as described above has the following characteristics. (A2) Density: 3.15g / cm 3 That's all. (B2) Thermal conductivity is 120 W / (m K) or more. (C2) The bending strength is 700 MPa or more. (D2) Fracture toughness is 6 MPa m 0.5That's all.
[0083] Thus, according to this modification, a silicon nitride substrate having a thermal conductivity of 120 W / (m K) or more and a bending strength of 700 MPa or more can be manufactured. Therefore, from the viewpoint of realizing a silicon nitride substrate with excellent performance, it is more desirable to adopt the manufacturing conditions in this modification rather than the manufacturing conditions in the embodied mode.
[0084] In the silicon nitride substrate manufactured under the manufacturing conditions of this modified example, based on the cumulative distribution of major axis diameter, the "microstructure" constituting the silicon nitride substrate can be quantitatively defined as shown below, assuming that a plurality of acicular particles with a major axis diameter of 10 μm or more are present on the fracture surface generated by a bending strength test. (1) L of the cumulative distribution of the major axis diameter of multiple acicular particles 50 is less than 31.5 μm. (2) L of the cumulative distribution of the major axis diameter of multiple acicular particles 90 is less than 70.0 μm. (3) The cumulative ratio of the major axis diameter of multiple acicular particles having a major axis diameter exceeding 100 μm is 2% or less.
[0085] The silicon nitride substrate containing the "microstructure" quantitatively defined as described above is This is because the silicon nitride substrate having the "microstructure" having the above-mentioned characteristics is a silicon nitride substrate manufactured under the manufacturing conditions of this modified example, and the silicon nitride substrate manufactured under the manufacturing conditions of this modified example has the above-mentioned characteristics.
[0086] Here, the quantification of the "microstructure" can be carried out not only based on the cumulative distribution of major axis diameters, but also based on the cumulative distribution of area. In the following, the quantification of the "microstructure" based on the cumulative distribution of area will be described in the same manner as in the embodiment.
[0087] In the silicon nitride substrate manufactured under the manufacturing conditions of this modified example, based on the cumulative area distribution, the "microstructure" constituting the silicon nitride substrate can be quantitatively defined as shown below, assuming that a plurality of acicular particles with a major axis diameter of 10 μm or more are present on the fracture surface generated by a bending strength test. (1) A of the cumulative area distribution of multiple acicular particles 50 is 165μm 2 The following is the result. (2) A of the cumulative area distribution of multiple acicular particles 90 is 450μm 2 The following is the result. (3) Area is 800 μm 2 The cumulative area ratio of multiple acicular particles exceeding 100% is 8% or less.
[0088] The silicon nitride substrate in this case also has the characteristics (A2) to (D2), because the silicon nitride substrate having a "microstructure" quantitatively defined based on the cumulative area distribution is the silicon nitride substrate manufactured under the manufacturing conditions in this modification, and the silicon nitride substrate manufactured under the manufacturing conditions in this modification has the characteristics (A2) to (D2).
[0089] <Example> Next, an embodiment will be described.
[0090] Table 1 shows the measured values of Examples 1 to 12, Examples 13 to 16, and Comparative Examples 1 to 12, and explains the results of comparison with the first specified condition.
[0091] [Table 1]
[0092] As shown in Table 1, it is found that the measured values of each of Comparative Examples 1 to 12 do not satisfy the first prescribed condition. As a result, it is found that each of Comparative Examples 1 to 12 does not achieve both a thermal conductivity of 110 W / (m K) or more and a bending strength of 600 MPa or more.
[0093] In contrast, it is seen that the measured values of each of Examples 1 to 12 and Examples 13 to 16 satisfy the first prescribed condition, as shown in Table 1. Therefore, it is seen that each of Examples 1 to 12 and Examples 13 to 16 achieves both a thermal conductivity of 110 W / (m K) or more and a bending strength of 600 MPa or more.
[0094] Here, for example, the density was measured by the underwater displacement method (Archimedes method). The bending strength was measured by preparing a test piece of 24 mm wide, 40 mm long, and 0.32 mm thick from the obtained silicon nitride substrate and performing a three-point bending test (span 36 mm, crosshead speed 0.5 mm / min), and the thermal conductivity (thickness direction) was measured by the flash method using a test piece cut into a 5 mm square. The fracture toughness was measured at room temperature in accordance with the IF method described in JIS R 1607.
[0095] Table 2 shows the measured values of Examples 1 to 12, Examples 13 to 16, and Comparative Examples 1 to 12, and explains the results of comparison with the second specified condition.
[0096] [Table 2]
[0097] As shown in Table 2, it is found that the measured values of Examples 13 to 16 and Comparative Examples 1 to 12 do not satisfy the second prescribed condition in some items. As a result, it is found that Examples 13 to 16 and Comparative Examples 1 to 12 do not achieve both a thermal conductivity of 120 W / (m K) or more and a bending strength of 700 MPa or more.
[0098] In contrast, it is seen that the measured values of each of Examples 1 to 12 satisfy the second prescribed condition, as shown in Table 2. Therefore, it is seen that each of Examples 1 to 12 achieves both a thermal conductivity of 120 W / (m K) or more and a bending strength of 700 MPa or more.
[0099] Thus, Examples 1 to 12 are examples that satisfy both the first and second prescribed conditions. On the other hand, Comparative Examples 1 to 12 are examples that do not satisfy either the first or second prescribed conditions. Moreover, Examples 13 to 16 are examples that satisfy the first prescribed condition but do not satisfy the second prescribed condition, which is stricter than the first prescribed condition.
[0100] The invention made by the inventor has been specifically described above based on the embodiment thereof. However, it goes without saying that the present invention is not limited to the above embodiment, and various modifications can be made without departing from the spirit of the invention. [Explanation of symbols]
[0101] 10 Silicon nitride substrate 10A Silicon nitride substrate 10B Silicon nitride substrate
Claims
1. A plurality of silicon nitride particles; a grain boundary phase present between the silicon nitride particles; A silicon nitride substrate comprising: The density of the silicon nitride substrate is 3.15 g / cm 3 That's all. In the fracture surface caused by bending strength test, A plurality of needle-shaped particles having a major axis diameter of 10 μm or more are present on the fracture surface, The L of the cumulative distribution of the major axis diameters of the plurality of acicular particles 50 is 33.0 μm or less, The L of the cumulative distribution of the major axis diameters of the plurality of acicular particles 90 is 72.0 μm or less, A silicon nitride substrate, wherein a cumulative ratio of the major axis diameters of the plurality of acicular particles having a major axis diameter exceeding 100 μm is 3.5% or less.
2. 2. The silicon nitride substrate according to claim 1, The L of the cumulative distribution of the major axis diameters of the plurality of acicular particles 50 is 31.5 μm or less, The L of the cumulative distribution of the major axis diameters of the plurality of acicular particles 90 is 70.0 μm or less, A silicon nitride substrate, wherein a cumulative ratio of the major axis diameters of the plurality of acicular particles having a major axis diameter exceeding 100 μm is 2% or less.
3. 2. The silicon nitride substrate according to claim 1, The thermal conductivity is 110 W / (m K) or more, The bending strength is 600 MPa or more, Fracture toughness is 6 MPa m 0.5 That is all about the silicon nitride substrate.
4. The silicon nitride substrate according to claim 2, The thermal conductivity is 120 W / (m·K) or more, The bending strength is 700 MPa or more, Fracture toughness is 6 MPa m 0.5 That is all about the silicon nitride substrate.
5. A plurality of silicon nitride particles; a grain boundary phase present between the silicon nitride particles; A silicon nitride substrate comprising: The density of the silicon nitride substrate is 3.15 g / cm 3 That's all. In the fracture surface caused by bending strength test, A plurality of needle-shaped particles having a major axis diameter of 10 μm or more are present on the fracture surface, A of the cumulative area distribution of the plurality of acicular particles 50 is 186 μm 2 is as follows: A of the cumulative area distribution of the plurality of acicular particles 90 is 560 μm 2 is as follows: Area is 800 μm 2 a cumulative area ratio of the plurality of acicular particles exceeding 12.5% or less.
6. The silicon nitride substrate according to claim 5, A of the cumulative area distribution of the plurality of acicular particles 50 is 165 μm 2 is as follows: A of the cumulative area distribution of the plurality of acicular particles 90 is 450 μm 2 is as follows: Area is 800 μm 2 a cumulative area ratio of the plurality of acicular particles exceeding 8% or less.
7. The silicon nitride substrate according to claim 5, The thermal conductivity is 110 W / (m K) or more, The bending strength is 600 MPa or more, Fracture toughness is 6 MPa m 0.5 That is all about the silicon nitride substrate.
8. The silicon nitride substrate according to claim 6, The thermal conductivity is 120 W / (m·K) or more, The bending strength is 700 MPa or more, Fracture toughness is 6 MPa m 0.5 That is all about the silicon nitride substrate.
9. (a) mixing a sintering aid with a silicon powder to prepare a mixed powder; (b) adding a dispersion medium to the mixed powder and pulverizing the mixture to prepare a slurry; (c) preparing a sheet-shaped compact using the slurry; (d) nitriding the silicon contained in the molded body; (e) after the step (d), a step of densifying and sintering the molded body; A method for manufacturing a silicon nitride substrate, comprising: In the silicon powder, Cumulative volume distribution d 10 is 1.0 μm or more and 2.5 μm or less, Cumulative volume distribution d 50 is 6.0 μm or more and 10.0 μm or less, Cumulative volume distribution d 90 is 12.0 μm or more and 20.0 μm or less, The specific surface area is 1.5 m 2 / g or more 3.0m 2 / g or less, In the mixed powder, Cumulative volume distribution d 50 is 2.0 μm or more and 6.4 μm or less, Cumulative volume distribution d 90 is 4.0 μm or more and 11.0 μm or less, The specific surface area is 4.5 m 2 / g or more 13.0m 2 / g or less, The heating temperature in the step (d) is 1340° C. or higher and 1450° C. or lower, The method for producing a silicon nitride substrate, wherein the heating temperature in the step (e) is 1850° C. or higher and 1950° C. or lower.
10. The method for producing a silicon nitride substrate according to claim 9, In the silicon powder, Cumulative volume distribution d 10 is 1.0 μm or more and 2.5 μm or less, Cumulative volume distribution d 50 is 6.0 μm or more and 9.5 μm or less, Cumulative volume distribution d 90 is 12.0 μm or more and 20.0 μm or less, The specific surface area is 1.5 m 2 / g or more 3.0m 2 / g or less, In the mixed powder, Cumulative volume distribution d 50 is 2.0 μm or more and 6.0 μm or less, Cumulative volume distribution d 90 is 4.0 μm or more and 9.2 μm or less, The specific surface area is 4.5 m 2 / g or more 13.0m 2 / g or less, The heating temperature in the step (d) is 1350° C. or higher and 1450° C. or lower, The method for producing a silicon nitride substrate, wherein the heating temperature in the step (e) is 1850° C. or higher and 1950° C. or lower.
Citation Information
Patent Citations
Method of manufacturing silicon nitride substrate and silicon nitride substrate
JP2018184333A